De novo assembly and annotation of the Amblyomma hebraeum tick midgut transcriptome response to Ehrlichia ruminantium infection - (:unkn) unknown (My University, 2023)
Bien que non co-auteur de cet article, ma contribution significative (assemblage de novo des séquences brutes en transcrits) a été reconnue dans la section Remerciements.AcknowledgmentsWe would like to extend our sincere gratitude to Peggy Hoffmann-Köhler from the Institute of Parasitology and Tropical Veterinary Medicine at the Freie Universität Berlin, whose technical expertise and logistical support were instrumental to this study. We are deeply appreciative of Cédric Cabau from the French National Institute for Agriculture, Food, and Environment (INRAE), who provided invaluable assistance with the de novo RNA-Seq Assembly Pipeline (DRAP) ...
Keywords: African Research